Systolic and Diastolic Ventricular Function Assessed by Tissue Doppler Imaging in Children with Chronic Kidney Disease. Issue 3 (20th November 2012) - Simpson, John M.; Rawlins, Debbie; Mathur, Sujeev; Chubb, Henry; Sinha, Manish D.
<x xml:space="preserve">Abstract</x> Chronic kidney disease (CKD) is associated with elevated cardiovascular risk even during childhood. Tissue Doppler is a sensitive technique for the assessment of ventricular dysfunction with relatively little data available in children with CKD. We report a prospective cross‐sectional echocardiographic study at a tertiary center. Forty‐nine patients with median (range) age 11.2 years (6.9–17.9), weight 39.6 kg (23.6–99.7) and height 146 cm (122–185). Thirty‐one patients were male. Median duration of follow‐up for CKD was 7.1 years (range 0.13–16.9). Patients were in CKD stage 3 (n = 37) or 4 (n = 12). Mitral valve E‐wave, A‐wave, and E/A ratio showed mean (SD) z‐scores of 0.08 (0.93), 0.12 (0.82) and −0.13 (0.84), respectively. Tissue Doppler imaging (TDI) at the lateral mitral valve annulus showed e′, a′, s′, and E/e′ z‐scores mean (SD) −1.10 (0.76), −0.29 (0.92), −1.2 (0.7), and 0.86 (1.1), respectively. There was a significant negative correlation of e′ and s′ z‐score with patient age. E/e′ ratio correlated positively with patient age. Blood pressure, left ventricular mass, and relative wall thickness did not correlate with tissue Doppler measurements. The e′ and s′ velocities correlated significantly with each other, suggesting an interaction of systolic and diastolic dysfunction. Children with CKD may have abnormalities of systolic and diastolic ventricular function on TDI, which are not evident on blood pool Doppler. The tissue Doppler results are consistent with worsening ventricular function in older patients.